Uneven geographic development of beer breweries in the United States - Veitch, Stanley Adam (Kansas State University, 2021)
Since the 1980s, beer brewing has diversified into craft products while continuing to feature large firms who produce vast quantities of mass-produced style beers. With this growth in the industry, different parts of the U.S. have seen uneven development of its brewing industries. To date, there has been little sociological analysis of the role that this expansion has played in local economies across the U.S. This study performs an exploratory analysis of the geographic distribution of beer breweries in the U.S. in 1990 and 2010. To understand the geographic distribution and relative concentration of breweries across the U.S. during this period, commodity chain analysis is used to examine production and consumer linkages in the beer commodity chain of the U.S in the year 2010. It is hypothesized that upstream and downstream components related to the commodity chain of brewing, including populations with cultural capital and the creative class, are correlated with the brewing industry’s relative concentration in different counties in the U.S. Multinomial and binary logistic regression analyses were performed on these upstream and downstream linkages (via the location quotient of breweries) to examine each of the variables’ importance to relative concentration of beer breweries in each county.
Keywords: Sociology; Social stratification; Social geography; Cultural sociology; Quantitative sociology